2019
DOI: 10.3389/fimmu.2019.00472
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoid Receptor-Deficient Foxp3+ Regulatory T Cells Fail to Control Experimental Inflammatory Bowel Disease

Abstract: Activation of the immune system increases systemic adrenal-derived glucocorticoid (GC) levels which downregulate the immune response as part of a negative feedback loop. While CD4+ T cells are essential target cells affected by GC, it is not known whether these hormones exert their major effects on CD4+ helper T cells, CD4+Foxp3+ regulatory T cells (Treg cells), or both. Here, we generated mice with a specific deletion of the glucocorticoid receptor (GR) in Foxp3+ Treg cells. Remarkably, while basal Treg cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 52 publications
(73 reference statements)
3
24
0
Order By: Relevance
“…While T REG cell adaptation at inflammatory sites is highly beneficial to the host, as uncontrolled inflammation may lead to increased localized and systemic damage, it can also be exploited by tumors to pro- inflammatory bowel disease, although it is not required for their suppressive ability. 133 Rapamycin, described as a potent Foxp3-inducing drug 134 and one of the most successful T REG modulatory drug, inhibits the mTOR pathway which in turn promotes OXPHOS over glycolysis and inhibits HIF-1 transcription, 135 suggesting that this drug can modify key components of T REG adaptation in order to "skew" them toward displaying their suppressive functions. Further investigation on the effect of these drugs on the environmental sensing ability of T REG cells will be key toward establishing a better rationale for their use.…”
Section: Resultsmentioning
confidence: 99%
“…While T REG cell adaptation at inflammatory sites is highly beneficial to the host, as uncontrolled inflammation may lead to increased localized and systemic damage, it can also be exploited by tumors to pro- inflammatory bowel disease, although it is not required for their suppressive ability. 133 Rapamycin, described as a potent Foxp3-inducing drug 134 and one of the most successful T REG modulatory drug, inhibits the mTOR pathway which in turn promotes OXPHOS over glycolysis and inhibits HIF-1 transcription, 135 suggesting that this drug can modify key components of T REG adaptation in order to "skew" them toward displaying their suppressive functions. Further investigation on the effect of these drugs on the environmental sensing ability of T REG cells will be key toward establishing a better rationale for their use.…”
Section: Resultsmentioning
confidence: 99%
“…Steroids and glucocorticoids can enlarge Treg populations in the periphery stimulating their function ( 111 ). In fact, Treg lacking the glucocorticoid receptor lose their suppressive function turning into Th1-like, IFNγ-producing cells in a murine colitis model ( 112 ).…”
Section: Treg Homeostasis and Function In Agingmentioning
confidence: 99%
“…GCs are well‐known for their general anti‐inflammatory effects, but beyond their production in adrenal glands, crypt IECs have been shown to release GCs in response to anti‐CD3‐mediated T‐cell activation, and IEC synthesis of GCs has been shown to control local inflammation and disease severity in a 2,4,6‐trinitrobenzene sulphonic acid colitis model . As almost all vertebrate cells express glucocorticoid receptors (GRs) the effects of GCs are pleiotropic; however, T‐cell‐specific responses to GCs have been shown to be involved in T‐cell homeostasis, and regulatory T (Treg) cell‐specific GR deficiency was recently shown to impair Treg cell capacity to prevent the induction of disease in a mouse model of inflammatory bowel disease . In addition, a recent study of mice with diminished GR responses revealed an interferon‐specific gene signature in the gut that was abrogated by antibiotic treatment, indicating a role for the microbiota .…”
Section: Iec–immune Cell Crosstalkmentioning
confidence: 99%
“…76,77 As almost all vertebrate cells express glucocorticoid receptors (GRs) the effects of GCs are pleiotropic; however, T-cell-specific responses to GCs have been shown to be involved in T-cell homeostasis, and regulatory T (Treg) cell-specific GR deficiency was recently shown to impair Treg cell capacity to prevent the induction of disease in a mouse model of inflammatory bowel disease. 78,79 In addition, a recent study of mice with diminished GR responses revealed an interferon-specific gene signature in the gut that was abrogated by antibiotic treatment, indicating a role for the microbiota. 80 While information regarding intestinal production of GCs continues to emerge, the stimuli involved and immune cell effects have yet to be fully elucidated.…”
Section: Iec Secretion Of Immunomodulatory Moleculesmentioning
confidence: 99%